Variasi Parameter Input Spot Welding Design dan Perubahan Nilai Tegangan Geser Sambungan Dissimilar Galvalum - Baja Karbon ST 41 - Ari Putra, I K.. Purnama; Budiarsa, I N.; Antara, I N. G. (Teknik Desain Mekanika, 2021)
Abstract This study aims to determine the effect of variations in the input parameters of Spot Welding Design and changes in the value of shear stress of Galvalume dissimilar joints - ST 41 Carbon Steel with Spot Welding Electrode Taper diameters of 6 mm and 7 mm. This study uses 3 test methods to determine the effect of variations in the input parameters of Spot Welding Design and changes in the value of shear stress and Galvalume dissimilar joints - ST 41 Carbon Steel with a Spot Welding Electrode Taper diameter of 6 mm and 7 mm, namely tensile tests for metals. (Base Metal), shear test on welded joints (Weld Joint). The results showed that the best shear strength value was found in specimen C (Ø 6mm, 3 volts, 0.5 seconds) with an average shear strength of 176.339 MPa and an average strain value of 0.041. Keywords: Spot Welding, Dissimilar, Tensile, Shear